Exosomal MiR-769-5p Exacerbates Ultraviolet-Induced Bystander Effect by Targeting TGFBR1 - Ni, Na; Ma, Weiwei; Tao, Yanling; Liu, Juan; Hua, Hui; Cheng, Jiawei; Wang, Jie; Zhou, Bingrong; Luo, Dan (Frontiers in Physiology, 2020)
Exosomal microRNAs have been investigated in bystander effect, but it is unclear whether microRNA works in ultraviolet-radiation induced bystander effects and what the underlying mechanism could be. Exosomes from ultraviolet irradiated human skin fibroblasts were isolated and transferred to normal HSFs, followed by the detection of proliferation rate, oxidative damage level and apoptosis rate. Exosomal miRNAs were evaluated and screened with miRNA sequencing and qRT-PCR method. MiRNA shuttle and bystander photo damage reaction were observed after transfection of miR-769-5p. MiR-769-5p targeting gene transforming growth factor-β1 (TGFBR1) and TGFBR1 mRNA 3′-UTR was assessed and identified by western blotting and dual luciferase reporter assay. Bystander effects was induced after being treated with isolated exosomes from UV irradiated HSFs. Exosomal miR-769-5p expression was significantly up-regulated. HSFs showed lower proliferation, increasing oxidative damage and faster occurrence of apoptosis after transfection. Exosome-mediated transfer of miR-769-5p was observed. Up-regulation of miR-769-5p induced bystander effects, while down-regulation of miR-769-5p can suppress UV-RIBEs. In addition, miR-769-5p was found to downregulate TGFBR1 gene expression by directly targeting its 3′-UTR. Our results demonstrate that exosome-mediated miR-769-5p transfer could function as an intercellular messenger and exacerbate ultraviolet-radiation induced bystander effects. MiR-769-5p inhibits the expression of TGFBR1 by targeting TGFBR1 mRNA 3'-UTR.